2020
DOI: 10.21203/rs.3.rs-24078/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SUV39H1-DNMT3A-mediated epigenetic regulation of Tim-3 and galectin-9 in the cervical cancer

Abstract: Background: Methylation of histone 3 at lysine 9 (H3K9) and DNA methylation are epigenetic marks correlated with genes silencing. The tumor microenvironment significantly influences therapeutic responses and clinical outcomes. The epigenetic-regulation mechanism of the costimulatory factors Tim-3 and galectin-9 in cervical cancer remains unknown. Methods: The methylation status of HAVCR2 and LGALS9 were detected by MS-PCR in cervical cancer tissues and cell lines. The underlying molecular mechanism of SUV39H1-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…The DNA methylation enrichment at the CREMα promoter of total T cells from SLE patients has been proved to be sharply lowered [2], and DNA methyltransferase 3a (DNMT3a) within the CREMα promoter region of SLE CD4 + T cells is greatly attenuated, while the H3K4me3 and SET domain containing 1 (Set1, an important H3K4 methyltransferase) bindings in this region are strikingly elevated [37]. As mentioned before, H3K9me3 can affect the levels of DNA methylation [19,20,[28][29][30] and H3K4 methylation [31][32][33]. According to these clues, we examined the H3K9me3 binding in the CREMα promoter region, and verified it was decreased in CD4 + T cells of SLE relative to normal controls.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The DNA methylation enrichment at the CREMα promoter of total T cells from SLE patients has been proved to be sharply lowered [2], and DNA methyltransferase 3a (DNMT3a) within the CREMα promoter region of SLE CD4 + T cells is greatly attenuated, while the H3K4me3 and SET domain containing 1 (Set1, an important H3K4 methyltransferase) bindings in this region are strikingly elevated [37]. As mentioned before, H3K9me3 can affect the levels of DNA methylation [19,20,[28][29][30] and H3K4 methylation [31][32][33]. According to these clues, we examined the H3K9me3 binding in the CREMα promoter region, and verified it was decreased in CD4 + T cells of SLE relative to normal controls.…”
mentioning
confidence: 80%
“…Epigenetic mechanisms mainly involve DNA methylation, histone modification, chromatin remodeling, and regulation of noncoding RNA [12][13][14]. Studies have shown that H3 lysine 9 trimethylation (H3K9me3) [15][16][17][18] and DNA methylation [19][20][21][22] lead to transcriptional inhibition, while H3 lysine 4 trimethylation (H3K4me3) is related to transcriptional activation [23,24]. Of these, H3K9me3, as one of the most common histone modifications leading to transcriptional repression, has been a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation in the promoter region can directly interfere with the binding of transcription factors to cis-acting elements, leading to a decrease in gene transcription. In addition, DNMT1 [19] and DNMT3a [20] can change the chromatin structure and inhibit gene transcription by binding to the histone methyltransferase SUV39H1. Methylation mediated by MBPs is the most common form of gene expression silencing caused by DNA methylation.…”
Section: Dna Methylation-relatedmentioning
confidence: 99%
“…The ChIP experiments were executed using the Simple ChIP Enzymatic Chromatin IP Kit (Cell Signaling Technology, USA) as previously [11], in brie y, 1×10 7 cells were cross-linked with 1% formaldehyde for 10 minutes at room temperature. The crosslinking was then quenched with 10×glycine.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…Tumor growth and mouse weight was monitored until death. Tumor volume was calculated as previously described [11], using the following formula: tumor volume (mm 3 ) =0.5×length×width 2 . Mice were monitored for 15 days, at which time mice were euthanized and tumors and organs were extracted.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%